Early computer awareness courses in australian secondary schools : Curricula from the late 1970s and early 1980s - Tatnall, Arthur (2006)
Today there is no need to introduce secondary school students to computer technology, but in the early 1980s, the situation was quite different. In Australia in the late 1970s and early 1980s considerable importance was put on the introduction of Computer Awareness courses in secondary schools. The justification for such courses was the perceived need for children to be prepared for living in a society which was fast becoming dependant on the widespread application of computer technology, and that few people then understood the use and implications of this technology. Unlike in parts of the United States, no distinction was made in Australia between Computer Awareness and Computer Literacy, with the Australian curricula involving elements of each. This paper outlines the reasons for the development of Computer Awareness courses in Australia and describes their content. It discusses the consequences of these courses and why they were prominent in the 1980s.